ANALISIS KONFLIK BUDAYA POLITIK DI PAPUA: PERSPEKTIF POLITIK MULTIKULTURALISME DAN KONFLIK POLITIK IDENTITAS - Suharizal, Suharizal (Ensiklopedia of Journal, 2025)
Abstract: The Papua region has a rich culture and unique customs that differentiate it from other regions in Indonesia. However, the implementation of development policies by the central government often gives rise to polemics, especially when local needs and identities are not accommodated. This article aims to analyze development policy conflicts in Papua from a multicultural political perspective. Using a qualitative analysis approach, the discussion includes the dominance of majority identity, social exclusion, recognition of local identity, inclusive policies, and the conflict between national principles and local autonomy. The conclusion shows that development in Papua requires policies that are inclusive, respect local identity, and involve the active participation of local communities. A multicultural approach can be a solution in creating harmony between national development and local cultural diversity.Keywords: Conflict, Political Culture, Papua.